Disaster culture : knowledge and uncertainty in the wake of human and environmental catastrophe - Button, Gregory (Left Coast Press, 2010)
Drawing on decades of research on the most infamous human and environmental calamities, Button shows how states, corporations, and other actors attempt to create meaning and control social relations in post-disaster struggles for the redistribution of power.